PENGARUH PENERIMAAN PAJAK HOTEL, PAJAK RESTORAN, RETRIBUSI TEMPAT REKREASI DAN OLAHRAGA, DAN HASIL PENGELOLAAN KEKAYAAN DAERAH YANG DIPISAH TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN KLATEN TAHUN 2011 - 2016 - wahyuningsih wahyu (Program Studi Manajemen Fakultas Ekonomi UST, 2018)
This study aims to determine the effect of hotel taxes, restaurant taxes, retribution places of recreation and sports, and the result of separated regional wealth management of local revenue. Research is quantitative. Pupolasi in this research is hotel, restaurant, place of recreation and sport, and result of separated area wealth management residing in Regency of Klaten during period 2011 to 2016. The sample in this research is determined pursuant to purposive sampling which produce 4 sample of hotel tax, restaurant tax, retribution of recreation and sports, and the result of separated wealth management. The type of data used is secondary data obtained from the Regional Revenue Management Office. Data analysis technique used is multiple linear regression analysis. The result of double linear regression test shows that hotel taxes restaurant tax, retribution place of recreation and sport, and result of management of area wealth which separated simultaneously influence 44,43% to dependent variable while the rest influenced by component of research variable. While the partial, hotel tax has a positive effect on the local revenue with t count equal to -2.082 <2,500 and significant value 0.041> 0.05, restaurant tax does not affect the original income of t table area is -0.893 <2,500 and significant value 0.375> 0.05, retribution place of recreation and sport does not have an effect on to the original revenue of area t table that is equal to 0185 <2,500 and significant value 0,075> 0,05, and result of separated area wealth management does not have an effect to original income of area t table that is 0,855> 0,05 and significant value -0.184 < 2,500. Keywords: hotel tax, restaurant tax, retribution place of recreation and sport, result of management of region of origin separated by local revenue (PAD).